Peasant women and social security: advances and counter-reforms in Brazil - Souza, Roseli (Argumentum, 2024)
This article investigates the gains and losses of rights in the relationship between peasant women and social security in Brazil. It highlights the importance of social security using historical milestones including, the late arrival of these benefits in the countryside, the advances within the Federal Constitution of 1988, the limits imposed by the expansion of neoliberalism, the counter-reforms of recent years, and the impacts of limited access to social security on the rural population in times of capital crisis. The article is based on a bibliographic documentary review and field research through semi-structured interviews with women, carried out during the author's master's degree. It concludes that social security is fundamental and that it has a profound impact on the lives of the population, especially peasant women, but that access to it is currently limited due to the ongoing counter-reforms.